Wideband high‐gain circularly polarized Fabry‐Perot antenna feeding a conical short‐horn. Issue 9 (8th October 2018) - Ge, Yuehe; Qin, Kaiyuan
Abstract: In this article, a novel wideband high‐gain circularly‐polarized (CP) antenna is developed. It is based on a Fabry‐Perot (FP) resonant cavity with a small footprint and a small slot‐fed CP antenna designed to achieve wideband high gain CP performance. This is then used to feed a short conical horn to enhance the overall gain without compromising the radiation performance. Simulations and measurements are in good agreement and validate the predictions. The measurement of the antenna prototype demonstrates a more than 3 dB gain enhancement when the conical horn is used.